Pengaruh Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi Dan Kesenjangan Antar Daerah Serta Penyerapan Tenaga Kerja Dan Kesejahteraan Di Kabupaten / Kota Di Provinsi Jawa Tengah - Hadi Sasana, - (2008)
During the era of local autonomy and fiscal decentralization, local governments is provided with authority to increase their income and to conduct allocative function in setting priority of local development. This research is intended to examine the influence of fiscal decentralization on economic growth, inter-regional inequality. employment, and welfare at regencies/municipalities level in Central Java Province. Research population consist of29 regencies and 6 municipalities, employing secondary data from Central Bureau of Statistic of Central Java Province and regencies/municipalities level in Central Java Province within the period of2001 up to 2005. Data analysis is conducted by using path analysis with SPSS program software. The results of this study indicate that, first fiscal decentralization has a positive and significant effect on economic growth at regencies/municipalities level in Central Java Province. Second, fiscal decentralization has a negative and significant effect on inter-regional inequality at regencies/municipalities level in Central Java Province. Third, economic growth has a negative and significant effect on inter-regional inequality at regencies/municipalities level in Central Java Province. Forth, economic gro\Vth has a positive and significant effect on employment rate at regencies/municipalities level in Central Java Province. Fifth, economic growth has a positive and significant effect on welfare at regencies/municipalities level in Central Java Province. Sixth, inter-regional inequality has a negative and significant effect on welfare at regencies/municipalities level in Central Java Province. Seventh, employment rate has a negative and significant effect on welfare at regencies/municipalities level in Central Java Province.